EVALUATION OF STUDENTS’ PERCEPTION OF BIOLOGY CLASSROOM LEARNING ENVIRONMENT - Loh Su Ling; Vincent Pang; Denis Lajium, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Students’ feedback about their classroom learning environment can be used to provide information about the strengths and problems that need to be addressed. This study assessed the students’ perceptions of their biology learning environment. The difference between male and female students’ perceptions of their learning environment was also investigated. Learning environment instrument What is Happening in this Class (WIHIC) questionnaire was employed to evaluate the perception of 437 Form Four students who took Biology as one of their subjects in a local district. The data were analysed based on the Rasch (1961) measurement model using the Winsteps software. Overall, the students perceived quite favourably on their biology classroom learning environment. Apart from that, there is no difference between the boys and girls in their general perception of the biology classroom learning environment. Further analysis on each scale showed the scales of Students Cohesiveness and Cooperation were perceived positively in the Biology classroom. However, students find it difficult to agree on the scale of Investigation and Involvement. DIF analysis of the items revealed some differences in their perceptions in the scales as well as some of the items between male and female students. Several suggestions were given in the hope of improving and create an effective classroom learning environment. With such feedbacks, Biology teachers and the school administration can strive to improve and create an effective classroom learning environment, provide useful background information for further evaluation phases and inform on the best approach to carry out Biology lessons in the classroom.